Identifying sources of groundwater and recharge zone using stable environmental isotopes in the Erbil basin-northern Iraq - Bruska S. Mamand; Dana K. Mawlood (Kuwait Journal of Science)
The Dashty-Hewler basin is a groundwater basin located in Erbil in northern Iraq. It comprises three distinct sub-basins (Kapran, Central, and Bashtapa) covering a total basin area of 2,660 ​km2. It is bounded by the greater Zab river to the north and the little Zab to the south. The groundwater in this catchment has never been investigated using modern environmental isotope evidence. Since the groundwater in this basin serves as both drinking water and a source of irrigation, its management is crucial. Recently, due to the increase in population, excessive pumping has taken place, which has led to a decline in the water table. Accordingly, it is necessary to address the issues of where the groundwater will recharge and what the source of the recharge will be. For this purpose, 27 groundwater samples from different wells and two river water samples were analyzed for stable isotopes (δ18O and δ2H). The distribution of δ18O and δ2H over the study area was utilized by inverse distance weighted (IDW) interpolation within ESRI ArcGIS (10.8). The results indicated that the relationship between δ18O and δ2H in the groundwater samples (δ2H ​= ​6.59 δ18O +7.48‰) showed relative shifts of both the slope and the deuterium excess when compared to the Iraq meteoric water line (δ2H ​= ​7.66 δ18O ​+ ​14.19‰). The deviation of data points from the meteoric line can be attributed to high evaporation both during the rainy season and through run-off on the ground surface before infiltration. Most of the groundwater samples had a deuterium excess above 10‰ between 12.14 and 22.72‰, suggesting the precipitation present in the groundwater comes from the Mediterranean sector. Based on local isotopic gradients (δ18O, −0.22/100 ​m), in combination with topographic and geologic criteria, the recharge areas were identified as being between 400 ​m and 1,100 ​m above sea level.